DEVELOPMENT CURRICULUM BASED EDUCATION CHARACTER - Basit, Moh. Al (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Character-based curriculum development is an activity that seeks to compile or design a new curriculum, change and perfect or improve the curriculum, implement the curriculum, and control the basic education curriculum. This control includes monitoring and evaluating the curriculum, as well as improving the curriculum based on input from the results of monitoring and evaluation of the basic education curriculum that has been practiced in school and out-ofschool educational institutions with various types and varieties. The values that are used as the basis for curriculum development must come from religious values, Pancasila, culture, and national education goals. The values derived from the four pillars are embodied in 18 values, namely Religious, Honest, Tolerance, Discipline, Hard Work, Creative, Independent, Democratic, Curiosity, National Spirit, Love of the Motherland, Respect for Achievement, Friendly or Communicative, Love Peace, Love to Read, Care for the Environment, Care for the Social, and Responsibility.